Rational construction of a metal core for smart combination with Li4Ti5O12 as integrated arrays with superior high-rate Li-ion storage performance. Issue 4 (5th January 2017) - Zhou, Cheng-ao; Xia, Xinhui; Wang, Yadong; Zhong, Yu; Yao, Zhujun; Wang, Xiuli; Tu, Jiangping
Abstract : Co/Li4 Ti5 O12 arrays with a bamboo joint-like core and hollow tube shell are prepared via ALD-lithiation and they demonstrated excellent high-rate performance. Abstract : Directional design/fabrication of advanced high-rate electrodes is critical for the development of high-performance electrochemical energy storage devices with large energy/power densities. In this work, we for the first time realize a bamboo joint-like metal Co core for smart combination with spinel lithium titanate (Li4 Ti5 O12, LTO) in free-standing core/shell arrays with the help of atomic layer deposition (ALD) plus lithiation. Combined properties such as improved electrical conductivity, enhanced structural stability, and large hollow structures are achieved in the Co/LTO core/shell architecture. Owing to the well-designed structure, the binder-free core/shell arrays of Co/LTO exhibit impressive performance with excellent high-rate performance (146 mA h g −1 at 50C and 143 mA h g −1 at 100C) and remarkable cycle life (142 mA h g −1 after 3000 cycles at 20C with 90% retention). Our newly developed metal-based core/shell arrays have put on a new look on the construction of advanced hetero-structured electrodes.